Association of Hepatitis C Virus (HCV) Infection and Human Leukocyte Antigens (HLA) - Abdul-Razak SH Hasan; Karim Sadun Ali Al-Ajeeli (Diyala Journal of Medicine, 2019)
Back ground: Several previous reports on the association between hepatitis C virus (HCV) infection and certain human leukocyte antigens (HLA) have yielded controversial results.